Anakinra Pilot – a clinical trial to demonstrate safety, feasibility and pharmacokinetics of interleukin 1 receptor antagonist in preterm infants - Green, Elys A.; Metz, David; Galinsky, Robert; Atkinson, Rebecka; Skuza, Elizbeth M.; Clark, Megan; Gunn, Alistair J; Kirkpatrick, Carl M.; Hunt, Rod W.; Berger, Philip J.; Nold-Petry, Claudia A.; Nold, Marcel F. (Frontiers in Immunology, 2022)
Background: Bronchopulmonary dysplasia (BPD), its complication pulmonary hypertension (BPD-PH) and preterm brain and gut injury lead to significant morbidity and mortality in infants born extremely prematurely. There is extensive evidence that the pro-inflammatory cytokine interleukin 1 (IL-1) plays a key role in the pathophysiology of these illnesses. Two decades of clinical use in paediatric and adult medicine have established an excellent safety and efficacy record for IL-1 blockade with IL-1 receptor antagonist (IL-1Ra, medication name anakinra). Building on robust pre-clinical evidence, the Anakinra Pilot trial aims to demonstrate safety and feasibility of administering anakinra to preterm infants, and to establish pharmacokinetics in this population. Its ultimate goal is to facilitate large studies that will test whether anakinra can ameliorate early-life inflammation, thus alleviating multiple complications of prematurity. Methods and analysis: Anakinra Pilot is an investigator-initiated, single arm, safety and feasibility dose-escalation trial in extremely preterm infants born between 24 weeks 0 days (240) and 276 weeks of gestational age (GA). Enrolled infants will receive anakinra intravenously over the first 21 days of life, starting in the first 24 h of life. In the first phase, dosing is 1 mg/kg every 48 h, and dosage will increase to 1.5 mg/kg every 24 h in the second phase. Initial anakinra dosing was determined through population pharmacokinetic model simulations. During the study, there will be a planned interim analysis planned to confirm predictions before undertaking dose assessment. Anakinra therapy will be considered safe if the frequency of adverse outcomes/events does not exceed that expected in infants born at 240-276 weeks GA. Ethics and dissemination: Ethics approval was granted by the Monash Health Human Research Ethics Committee. The findings of this study will be disseminated via peer-reviewed journals, presented at conferences and reported back to participants and consumers, for example via lay media. Trial Registration Number: NCT05280340